Pemanfaatan Vlog dalam Penyampaian Informasi Publik Pemerintah Kota Semarang - Martha Tri Lestari; Lisa Aji Sasmita (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2020)
This study aims to determine how to convey information from the Semarang City government to the public based on the sources used, relevant to people's lives, delivery of information based on the latest facts and accountable information, proximity to the community, and the use of the 5W + 1H formula. This research uses descriptive qualitative research methods. The results showed that the Semarang City Government used YouTube and vlogs as a medium for delivering information to the public by creating vlog content